Optimisasi Rute Distribusi Gas LPG 3 Kg Pada PT Arafizza Sikumbang Menggunakan Model VRP dan Algoritma Clarke and Wright Savings - Fani Indriyani Ningsih; Rina Filia Sari (Mandalika Mathematics and Educations Journal, 2025)
This study aims to optimize the distribution of 3 kg LPG cylinders at PT Arafizza Sikumbang, Medan Selayang District, Medan City. Efficient distribution is important to prevent shortages and reduce operational costs. The company serves 12 bases using Colt Diesel vehicles. The Vehicle Routing Problem (VRP) model with the Clarke and Wright Savings Algorithm was applied to improve delivery route efficiency. The data used was secondary data from December 2024, including distribution center locations, demand, vehicle capacity, and transportation costs, processed using Google Maps API and Microsoft Excel to create distance matrices and savings matrices. The initial route of 110.1 km with a cost of Rp 74,868 was successfully optimized to 90.9 km and Rp 61,812, achieving savings of 17.44% in distance and 17.4% in cost. These results demonstrate the effectiveness of the algorithm in improving LPG distribution efficiency and are relevant for application in similar logistics cases.